2016
DOI: 10.1111/aos.13060
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pseudoprogression after corneal cross‐linking in children with progressive keratoconus

Abstract: Our results confirm that CXL is effective in stabilizing keratoconus in children. True progression after CXL could only be verified in two of 33 eyes in a follow-up period of 37.5 months (SD ± 10 months). Two different measuring methods can help to detect diagnostic discrepancies and prevent false conclusions. Moreover, limbal vernal changes can cause transient pseudoprogression, reversible upon sufficient treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Above-mentioned studies did not have data for 36-month follow-up. In Schuerch et al 6 study, 5 cases of 33 (15.15%) eyes in a follow-up period of 37.5 months had an increase of 1 D or more of Kmax. Chatzis and Hafezi 18 investigated at 1, 2 and 3 years after C-CXL, Kmax readings were increased by 1 D or more in 11%, 13% and 55% of eyes.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Above-mentioned studies did not have data for 36-month follow-up. In Schuerch et al 6 study, 5 cases of 33 (15.15%) eyes in a follow-up period of 37.5 months had an increase of 1 D or more of Kmax. Chatzis and Hafezi 18 investigated at 1, 2 and 3 years after C-CXL, Kmax readings were increased by 1 D or more in 11%, 13% and 55% of eyes.…”
Section: Discussionmentioning
confidence: 88%
“…Corneal cross-linking (CXL) can increase the biomechanical strength and stability of the cornea by an interaction of ultraviolet (UV) light and riboflavin, which is used to halt or decelerate the progression of keratoconus. 5 Previous studies 6–10 have reported that conventional corneal collagen cross-linking (C-CXL; epithelium-off procedure with 3 mW/cm 2 UVA radiation for 30 min) is an effective and safe procedure to treat adult and paediatric keratoconus. Only a few studies 11 12 have investigated the use of accelerated transepithelial (ATE) CXL (ATE-CXL; epithelium-on procedure with 45 mW/cm 2 UVA radiation in the pulsed mode for 320 s) for the treatment of paediatric keratoconus.…”
Section: Introductionmentioning
confidence: 99%
“…Corneal CXL is a relatively new and promising treatment that halts the progression of the disease at the corneal ectasia stage. Several studies [ 7 10 ] have provided evidence that CXL is safe and effective in slowing or halting the progression of keratoconus,but most of these studies examined conventional CXL (C-CXL). To our knowledge, this study is the first to report the safety and efficacy of ATE-CXL in pediatric keratoconus patients.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal collagen cross-linking (CXL) can halt the progression of keratoconus by increasing the biomechanical rigidity of the corneal stroma via an interaction of riboflavin and ultraviolet radiation (UV) [ 5 , 6 ]. Many publications have reported on the safety and efficacy of CXL in the treatment of pediatric keratoconus patients [ 7 10 ], but treatment by accelerated transepithelial corneal collagen cross-linking (ATE-CXL) [ 11 , 12 ], which maintains the integrity of the corneal epithelium layer in pediatric keratoconus patients with a higher irradiation intensity of UV light and a reduced duration of irradiation, has not reported. The present study aimed to assess the safety and efficacy of ATE-CXL in children with progressive keratoconus.…”
Section: Introductionmentioning
confidence: 99%
“…Another CXL drawback is the prolonged treatment time that is required based on the Dresden protocol. Studies on CXL effectiveness have illustrated variable and sometimes adverse outcomes, such as worsening of topographic and pachymetric values [ 11 , 12 ]. Perhaps the most important drawback related to CXL is the fact that it is not suitable for every single patient with KC.…”
Section: Introductionmentioning
confidence: 99%